Forms of Operative and Service Activities of the Ukraine’s State Border Guard Agencies (Units): Concepts and Legal Regulation - V. V. Polovnikov (Law and Safety, 2019)
As the objective of this article, the characteristics of the concept and legal regulation of the Ukrainian state border guard agencies’ (units) operative and service activities forms are chosen. Such activity is a type of law enforcement activity. The level of the rule of law compliance of such agencies (units) officials and official persons’ service activities depends on the state of its legal regulation.